Fracture strength of lithium disilicate crowns compared to polymer-infiltrated ceramic-network and zirconia reinforced lithium silicate crowns. (October 2017) - Sieper, Kim; Wille, Sebastian; Kern, Matthias
Abstract: Objectives: The aim of this study was to evaluate the fracture strength of crowns made from current CAD/CAM materials. In addition the influence of crown thickness and chewing simulation on the fracture strength was evaluated. Methods: Crowns were fabricated from lithium disilicate, zirconia reinforced lithium silicate (ZLS-ceramic) and a polymer-infiltrated ceramic-network (PICN) with an occlusal thickness of 1.0 mm or 1.5 mm, respectively (n=16). Crowns were cemented on composite dies. Subgroups of eight specimens were loaded with 5 kg in a chewing simulator for 1, 200, 000 cycles with thermal cycling. Finally, all specimens were loaded until fracture in a universal testing machine. Three-way ANOVA was used to detect statistical interaction. Differences regarding the materials were tested with two-way ANOVA, following one-way ANOVA and a post-hoc Tukey's-Test. Results: All crowns survived the chewing simulation. The material had a significant influence on the fracture resistance (p≤0.05). Lithium disilicate achieved the highest values of fracture strength in almost all groups followed by ZLS-ceramic. PICN achieved the lowest values of fracture strength. Chewing simulation increased the fracture strength of thick lithium disilicate crown significantly. Greater occlusal thickness of all crown materials resulted in higher crown fracture strength before chewing simulation. After chewing simulation occlusal thickness of lithium disilicate and PICN crowns had no significant influence on the fracture strength. Conclusions: All crowns revealed fracture strength above the clinically expected loading forces. Therefore the durability of the tested CAD/CAM materials seems promising also in an occlusal thickness of 1.0 mm.